Hubungan Antara Model Pengasuhan ABC’s dengan Micro Badge Balanced Use of Technology pada Pembelajaran Daring di Masa Pandemi - Indri Sudanawati Rozas; Devi Oktaviani; Nur Isnaini; Wiwin Luqna Hunaida; Imas Maesaroh (Systemic: Information System and Informatics Journal, 2021)
Online learning methods can indeed be an alternative solution to the pandemic situation, but that doesn't mean it's without risks. Cyber ​​risks can vary widely, ranging from cyberbullying, victimization, game addiction, privacy concerns, harmful content, and also eye health problems. These risks can cause serious problems, especially for children aged 5 to 12 years. One of the guidelines for the parental involvement model to assist the healthy use of information technology is ABC's. ABC is an acronym for Age-Appropriate Access, Balance, and Content Restricted. In the ABC's model, specific recommendations and examples are given on how to set boundaries so that the use of technology remains healthy and useful. On the other hand, the Digital Quotient (DQ) Institute provides a micro-certification system called the DQ Micro-Badge (DQ MB) which is listed in the IEEE 3527.1-2020 standard. DQ MB is used to assist in the assessment of a person's digital skills according to the Global Standards. This study measures the relationship between ABC's parenting method and the achievement of DQ MB Balanced Use of Technology. Respondents used are parents who have children aged kindergarten - elementary school in the city of Surabaya. From 379 respondents' data, it was analyzed and obtained the fact that parenting using ABC's approach is proven to affect the level of digital intelligence based on the DQ MB Balanced